Specific binding of phorbol ester tumor promoters to intact primary epidermal cells from Sencar mice. - V. R. Solanki; Thomas J. Slaga (1981)
The binding of [20-3H]phorbol 12,13-dibutyrate ([3H]PDB) to intact living epidermal cells in monolayer culture was characterized. At 37 degrees C, the maximum specific [3H]PDB binding (binding displaceable by 30 microM unlabeled PDB) was attained in 15--20 min and was followed by a rapid decrease (down regulation) of radioactivity bound to the cells. The activity lost by the cells during this decrease was found in the incubation medium. Prior exposure of cells to phorbol 12-myristate 13-acetate (PMA; 12-O-tetradecanoylphorbol 13-acetate) but not to phorbol for 2 hr at 37 degrees C caused approximately 55% reduction in the number of measurable binding sites for [3H]PDB. The down regulation was temperature sensitive; there was no loss of radioactivity after 1 hr at 4 degrees C. The specific binding of [3H]PDB at 4 degrees C reached equilibrium in 15--20 min and was saturable and freely reversible. At equilibrium, epidermal cells contained 1.2 x 10(5) binding sites per cell, and binding sites had a KD of 10 nM. Specificity of binding was shown by the observation that the biologically active phorbol esters PMA and 12-deoxyphorbol 13-decanoate inhibited the binding, whereas the inactive parent compound phorbol and the nonphorbol tumor promoter anthralin did not have any effect. The abilities of these compounds to inhibit [3H]PDB binding directly correlates with their tumor promoting activities. Epidermal cells exposed to retinoic acid or fluocinolone acetonide for 24 hr had similar [3H]PDB binding characteristics as untreated cells suggesting that inhibition of tumor promotion induced by these compounds is not mediated through alterations in the phorbol ester binding sites.